Hannah G. Solomon papers - Solomon, Hannah G. (Hannah Greenebaum), 1858-1942.
Correspondence, organizational records, speeches and writings, biographical and genealogical material, family papers, photographs, scrapbook, and printed matter chiefly relating to Solomon's founding of the National Council of Jewish Women, a result of her chairmanship of the Jewish Women's Congress of the World's Parliament of Religions during the World's Columbian Exposition, Chicago, Ill., in 1893. Also documents her involvement with the Chicago Woman's Club, other civic and women's organizations, and the Park Ridge School for Girls and her attendance at the International Council of Women in Berlin, Germany, in 1904.
Civic leader and founder of the National Council of Jewish Women.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chicago Woman's Club (Chicago, Ill.); National Council of Jewish Women; Park Ridge School for Girls (Park Ridge, Ill.); Civic improvement -- Illinois -- Chicago; Jewish women -- Societies and clubs; Schools -- Illinois -- Park Ridge; Women -- Societies and clubs; Women -- Illinois -- Chicago; Civic leaders